Avaliação de qualidade de vida de pacientes submetidos à angioplastia coronariana e elaboração de material educativo - Lima, Fernanda Maria Alves [UNESP] (2013)
Cardiovascular diseases remain as the leading cause of death worldwide, especially the coronary artery disease. Percutaneous transluminal coronary angioplasty (PTCA) is one of the most commonly used methods for treating such disease. Technological advances have made possible to perform safer procedures with reduced stay in the hospital. However, educational interventions are still needed concerning modifiable risk factors that lead to behavioral changes, treatment adherence, and better quality of life in terms of health. This study aimed at assessing the quality of life in terms of health in patients submitted to percutaneous transluminal coronary angioplasty by using the variables of the SF-36 questionnaire and developing leaflets on coronary angioplasty and healthy lifestyles. Forty-five patients hospitalized in Botucatu Medical School Hospital – UNESP who were undergoing the procedure for the first time were included in the study. The data collection occurred twice from January to May 2012. The patients were evaluated regarding their quality of life before the coronary angioplasty (M1) and from 30 to 40 days after it (M2). Leaflets on PTCA and healthy lifestyles were designed to assist guiding such patients. The participants were in average 60.8 years old, mainly male (60%), and had low educational backgroun (in average, 5.1 years of study). Among the key risk and comorbidity factors were systemic hypertension (77.8%), sedentarism (71.1%), and dyslipidemia (60%). The average scores of the SF-36 were higher at M2, with statistically significant differences in all domains except in the Emotional Aspects. The patients related that the guidance offered, together with the leaflets, were highly important because not only did they clarify many doubts, but they also aided in several changes in their health habits, such as reduction in their intake of deep-fried foods/fatty meat (53.3%) and reduction of salt in their food ...